A study on the effects of interfering with the conventional sequential protocol for chemical isolation and characterization of chitosan from biowaste of giant freshwater prawn Macrobrachium rosenbergii. Issue 3 (March 2023) - Iber, Benedict Terkula; Torsabo, Donald; Chik, Che Engku Noramalina Che Engku; Wahab, Fachrul; Sheikh Abdullah, Siti Rozaimah; Abu Hassan, Hassimi; Kasan, Nor Azman
Abstract: Unless better measures are put in place to address the environmental and social impacts emanating from the huge waste generated from sea food processing industries; 'tragedy of the commons' is inevitable. Needless to re-emphasise the enormous contributions of aquaculture as the perfect substitute to capture fisheries which has been proven unsustainable. Be that as it may, the huge amount of bio-waste produced could be transformed into useful products such as chitin and chitosan with far reaching applications. Chitin and chitosan have been consistently processed from many sources following the traditional chemical sequence of Demineralization (DM), Deproteinization (DP), Decolouration (DC) and Deacetylation (DA). In this study, this method was re-ordered, resulting to 4 sequences of chemical processes. HCl, NaOH, ethanol (97%) and NaOH (50%) were used for DM, DP, DC and DA respectively. The results of this study showed that better chitin (23.99 ± 0.61%) and chitosan (15.17 ± 1.69%) yields were obtained from sequence four (SQ4) following the order of DC-DM-DP-DA. In addition, physicochemical properties such as DDA (80.67 ± 2.52%) and solubility (66.43 ± 2.61%) were significantly higher (p ≤ 0.05) in SQ4 thereby making the obtained product suitable for use as coagulant and flocculant in wastewater treatment. Results of FTIR, XRD and SEM of the study proved that the resultant product exhibited the characteristic nature of chitosan with porous and fibril nature. In the analysis of the physical properties of chitosan obtained from bio-waste of Macrobrachium rosenbergii, the high Carr's index (CI) and low bulk as well as tapped densities were an indication that the chitosan produced in this study had poor flowability and compressibility, thereby making it unfit for application in pharmaceutical industries. Graphical abstract: Image 1